EVALUASI SIFAT FISIK DAN DAYA IRITASI SEDIAAN LOTION MINYAK ATSIRI BUNGA CENGKEH (SYZIQIUM AROMATICUM) DENGAN BERBAGAI VARIASI KONSENTRASI - Fadzil Latifah; Nining Sugihartini; Tedjo Yuwono (Majalah Obat Tradisional, 2016)
In this study, the lotion contained essential oil of clove Syzigium a romaticum which contained eugenol as the active ingredient. Eugenol has been scientifically proven as anti-inflammatory. Because its activity, the study about development of dosage form is needed. Aims of this study was to know the physical properties of spreadibility, adhesivity, pH, viscosity and irritation index of lotion with variation concentration of essential oil.Thisstudywasstartedwithaformulationoflotionwith variationconcentrationofessentialoil5%(FI); 10% (FII); 15% (FIII). Lotion was evaluated physical properties with parameters spreadibility, adhesivity, viscosity and pH. The evaluation of iritation index was done using guinea pig test animals. Data were analyzed statistically with One Way Anova at confidence level of 95% to detect a significant difference between the treatment groups. The results of the study showed the variation consentration did not influence pH the increasing concentration caused a decreasing spredibility P<0.05 and increasing adhesivity P<0.05. The all of concentration did not irritated the skin of guinea pigs.